Exploring the Potential of Durian Seed Flour, Jack Bean Sprouts Flour, and Chia Seeds in Biscuits for Underweight Toddlers as an Alternative Complementary Foods - Izzati, Alfin Nur; Agustia, Friska Citra; Ramadhan, Gumintang Ratna; Dewi, Kifayati Rosiyanti; Walter, Ponjan (Universitas Ahmad Dahlan, 2025)
Biscuits with sufficient energy and protein can be provided as complementary feeding to meet the dietary needs of underweight toddlers. This study contributes to determine the effect of the proportion of durian seed flour, jack bean sprout flour, and chia seeds on the protein content, fat content, and hedonic quality of biscuits. This study uses the Completely Randomized Design (CRD) method with three biscuit proportions, with the ratio of durian seed flour:jack bean sprout flour:chia seeds T1 (35%:45%:5%), T2 (45%:35%:5%), and T3 (55%:20%:5%). Total protein and fat content testing were carried out in duplicate on each sample, 6 times, then analyzed using SPSS 25 using the ANOVA method and DMRT further test (p<0.05). While the hedonic test and hedonic quality were analyzed using the Friedman test followed by DMRT (p<0.05). The best treatment was selected based on the effectiveness index test. The proportion of durian seed flour biscuits, jack bean sprout flour, and chia seeds affects protein, fat, color quality, aroma quality, aftertaste quality, texture quality, aroma preference, aftertaste preference, texture preference, and overall preference. The best formula biscuit is biscuit with a proportion of 45% durian seed flour, 35% jack bean sprout flour, and 5% chia seeds, containing 459.28 kcal of energy, 15.33% db protein, 16.72% db fat, 61.87% db carbohydrates, 4.82% wb water, 1.26% db ash, and a serving size of 19 pieces biscuit will provide 20% of toddler daily protein requirements.